Guilt in response to blame from others - Parkinson, B; Illingworth, S (Taylor and Francis Group, 2009)
In three studies, participants rated appraisals and emotions experienced when someone else blamed them for something that was not their fault. Several participants spontaneously reported experiencing guilt in each study. Using event-contingent diaries, Study 1 found only weak correlations between rated self-blame and reported guilt when participants were blamed unreasonably. Using directed retrospective recall, Studies 2 and 3 found that guilt was higher in blamed than unblamed conditions when self-blame was low, and that the desire to apologise remained a significant predictor of guilt after controlling for all relevant appraisal dimensions. Taken together, these findings suggest that self-blame-related appraisals are not necessary conditions for the experience of guilt, and support an interpersonal analysis that sees this emotion as a strategy for repairing relationships after perceived (but not always genuine) slights.